A Multimodal Assessment of Tobacco Use on a University Campus and Support for Adopting a Comprehensive Tobacco-Free Policy - Wong, Samantha L. (Prev Med, 2020)
Many college campuses now prohibit tobacco use. At a private U.S. university, the current study assessed cigarette and e-cigarette use and characterized the climate for adopting a comprehensive tobacco-free policy. Data were gathered January-August 2018 via an: environmental scan; cigarette-urn audit; and representative surveys with campus community members. Despite low prevalence of tobacco (0.5%–8%) and e-cigarette use (0.9%–6%) among all groups, campus cigarette clean-up costs exceeded $114,000 for an estimated >1 million butts left on campus annually. A majority of respondents (63% of N=2218) favored a campus-wide tobacco-free policy, 16% opposed, and 21% abstained. Most respondents endorsed benefits of supporting health (93%), ensuring tobacco-free air to breathe (92%), reducing litter (88%), preventing tobacco use (84%) and fires (83%), and helping tobacco users quit (65%). Identified challenges included policy enforcement (69%) and stigmatization of smoking (57%); 30% viewed a policy as compromising personal freedoms. In a model explaining 35% of variance in policy support, those more likely to favor comprehensive tobacco-free campus policy were Asian respondents; diagnosed with asthma; exposed to secondhand smoke on campus; who viewed campus cigarette butt litter as problematic; and identified health, prevention, and cessation benefits of a tobacco-free campus. Those less likely in favor were students, those who smoke, and those perceiving impingement upon personal freedoms, stigmatization, and broader (slippery slope) implications. Findings indicate low tobacco use prevalence among the campus community, yet a large volume of butt litter and high tobacco clean-up costs. Predictors of policy support can inform campus outreach efforts.